Cross-dressing to backbeats: An exploration of the practices, wo/men producers, and history of electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.
https://spectrum.library.concordia.ca/id/eprint/977861/1/Madden_PhD_F2013.pdf
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; DIG; amériques; approches et analyses; communication; discipline; femmes* artistes; genre; historiographie; montréal; musique; mémoires/thèses; philosophie; point de vue situé; périodes historiques; recherche-création; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Young, Black and male : Exploring the intersections of racial and gender identity in an all-Black male high school - Rogers, Leoandra Onnie (New York University, 2012)
From popular culture to academia, there is national panic about the dismal life trajectories of Black males. This "Black male crisis" has contributed to emergent all-Black, all-male schools. Racial identity is commonly used to explain underperformance among Blacks, yet within-group gender disparity signifies the importance of gender relative to race. Minimal research exists on Black males' gender identities, and less on the intersections of gender and race. This longitudinal dissertation used quantitative and qualitative data to examine the development and intersections of racial and gender identity among Black adolescent males transitioning from co-educational grammar schools and entering the ninth grade at an all-Black, all-male high school. Findings are presented in two empirical papers. Paper 1 examined survey data collected from Black males (N = 183) to explain how boys' racial and gender identities were interrelated, changed over time, and influenced their psychological and academic adjustment. Results from the growth curve analysis revealed that boys' racial and gender identities were interrelated with each other and that higher levels of identity attachment were associated with better psychological and academic adjustment. Moreover, the strength of the relationship between gender identity and psychological adjustment increased over time, indicating that gender identity became increasingly important for boys' wellbeing. Paper 2 analyzed interview data with a subsample of Black males (n = 21) to examine how they resisted and accommodated racial and gender stereotypes. Results from the qualitative analysis revealed that boys were aware of the ways that racial and gender stereotypes overlap, but they responded to these stereotypes in different ways. Although some boys accommodated to both racial and gender stereotypes and others resisted these stereotypes, the majority of the boys responded by accommodating to gender stereotypes and resisting racial stereotypes. That is, they tended to perpetuate cultural stereotypes that require males to be the leader, emotionally stoic, and not to be feminine (i.e., gay) while challenging beliefs about the intellectual inferiority and incompetence of Black people. Findings are interpreted within the macro-context of cultural stereotypes and the micro-context of an all-Black male school. Implications for the study of identity, Black males, and single-sex education are discussed.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; adolescence; amériques; approches et analyses; chicago; discipline; genre; hommes* noirs; identité raciale; intersectionnalité; mémoires/thèses; philosophie; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes; étude longitudinale; étude qualitative; étude quantitative

Mais oui c'est un travail!: penser le travail du sexe au-delà de la victimisation - Parent, Colette; Bruckert, Chris; Corriveau, Patrice; Nengeh Mensah, Maria; Toupin, Louise (Presses de l'Université du Québec, 2010)
La question du travail du sexe fait toujours, aujourd’hui, l’objet de polémiques où le moralisme et les bons sentiments prévalent sur la discussion ouverte. La traite des femmes pour fins de « prostitution » et leur vulnérabilité physique face à la violence et à l’homicide débouchent souvent sur des demandes de répression accrue, et ce sont les travailleuses du sexe qui font les frais de ces discours prohibitionnistes et moralisateurs. Soucieux de véhiculer auprès d’un large public une vision différente de la « prostitution » dans le respect des travailleuses du sexe et de remettre en question les bases du message néo-abolitionniste qui présente ces dernières essentiellement comme des victimes de souteneurs ou de leur fausse conscience, cinq spécialistes ont entrepris la rédaction collective d’un livre pour démystifier plusieurs préjugés liés au travail du sexe. Sont abordés dans ce livre original les fondements du débat actuel de la « prostitution » comme travail, les différentes réponses des régimes juridiques, la variété de pratiques et d’expertises mises en oeuvre par les femmes elles-mêmes, incluant celles des migrantes illégales, et l’action collective des regroupements qui luttent pour une reconnaissance du travail du sexe. Mais oui c’est un travail ! invite donc à déconstruire certains mythes et stéréotypes, et à étayer la preuve à l’effet qu’il est non seulement possible de défendre la légitimité du travail du sexe tout en luttant contre la violence, mais que cela est nécessaire.
Section: xvii, 137 pages ; 23 cm
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; corps; corps féminin; cours; discipline; phi2030; philosophie; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution

Exploration of romantic relationships in adolescent females - Wisnieski, Deborah (The University of Oklahoma, 2009)
Adolescence is a time to explore and develop romantic relationships. Glamorized sexual messages and images bombard youth as they struggle to develop their sexual identity. The darker side of romance that includes teen pregnancy, STDs, and emotional pain is rarely portrayed. Because adolescent females shoulder the burden of unwanted sexual outcomes, an exploration of their experiences, both positive and negative, is the focus of this study. Current literature contains demographic information about who is at risk for unwanted pregnancies and Sexually Transmitted Diseases (STDs), but little is known from the adolescent females’ perspective, about their sexual experiences and even less about normal romantic ideation which drives sexual behavior. This qualitative study utilized ethnographic interviews to explore the experiences of 28 females ages 19-29 from four cultural backgrounds including Euro-American, African-American, American Indian, and Latina. The influence of families, peers, school, and sex education programs was explored for positive and negative experiences. Advice about romantic development to younger adolescent females was sought to gain insight into their development and how to better assist adolescent females in developing healthy romantic relationships. A multi-staged data analysis of the interviews was used to find similarities and differences among the subjects and cross culturally. Discussion of romantic behavior occurred in less than half of the nuclear families. Extended family such as aunts, uncles, and grandparents were named as significant role models by most participants and were frequently described as sources for support and occasionally available for discussion of romantic relationships. Peers were perceived to be sexually active and most behaved in a similar manner. Euro- and African-Americans placed more importance on peer groups. Reproduction was most frequently learned in the school system, rather than from family and peers. The programs were reported as woefully lacking in comprehensiveness. This study calls for policymakers to fund sex education programs for adolescents with potential participation from parents, extended family, and peers. The curriculum should address age-appropriate strategies for discussing romantic and sexual behavior. Additionally, guidelines for monitoring activities and use of new technologies that pose higher risks in early adolescence are most important. Health educators and healthcare providers can utilize these strategies when working with adolescents, families, and peers to improve their romantic relationships and decrease teen pregnancies and STDs.
Keywords: 2000 à aujourd'hui; 2000-2009; adolescentes*; amériques; discipline; mémoires/thèses; philosophie; périodes historiques; relations amoureuses; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexualité; thématiques; états-unis; étude qualitative

Le récit de soi - Butler, Judith (Presses universitaires de France, 2007)
Cet ouvrage renouvelle de manière fondamentale la pratique éthique, en affirmant avec vigueur que la réflexion morale ne saurait être considérée en dehors du contexte social et politique dans lequel elle est formulée. Si la philosophie morale a par nature tendance à idéaliser le sujet moral en lui conférant une autonomie trop vite considérée comme allant de soi, il importe de contrer cette tendance en prenant comme point de départ l'expérience indépassable du caractère relationnel de chaque vie. Aucune vie ne saurait se dire à soi, parvenant à construire le récit adéquat de son déroulement, ni revenir sur son émergence dans le monde. Ce qui se soustrait à elle, ce sont non seulement les conditions de sa naissance et de son développement, mais aussi les formes sociales qui la rendent lisible. La reconnaissance de soi par soi est incomplète, lacunaire. Située dans le récit des autres, elle est hantée par les formes de justification qui en découlent et achèvent de rendre toute procédure de reconnaissance impossible. Le rapport à l'autre devient constitutif de l'impossible rapport à soi. C'est dans ce contexte de dépossession qu'il devient urgent, selon Judith Butler, de procéder à une enquête sur les conditions de possibilité d'une relation morale à soi et aux autres qui ne fasse pas violence à un tel contexte mais le prenne au contraire en considération. Car l'éthique est violente dès lors qu'elle s'arroge le droit de dépasser les contextes singuliers dans lesquels se trouvent placées les vies pour formuler des prescriptions universelles.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; fem1000; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; états-unis; éthique

Gabriel Girard – Interview Elsa Dorlin : Le Queer est un matérialisme - Girard, Gabriel (Syllepse, 2007)
Interview d'Elsa Dorlin pour l'ouvrage "Femmes, genre, féminismes".
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; philosophie; philosophie politique; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; états-unis

Anti-Essentialism and Intersectionality - Grillo, Tina (Theorizing feminisms a reader, 2006)
'What is oppression ?' 'What should be done about it ?' Organized around these questions, Theorizing feminisms : a reader provides an overview of theoritical feminist writing about the quest for gender justice. Incorporating both classic and cutting-edge material, the reader takes into account the full diversity of women, highlighting the effects of race, ethnicity, nationality, class, sexuality, and religion on women's experience. Theorizing feminisms is organized into four sections and includes fifty-four essays. The first section introduces several basic concepts commonly employed when thinking about sexism - oppression, social construction, essentialism, intersectionality, gender, race, and class - and also raises questions about the perspective and legitimacy of the theorist. The second section surveys three approaches that attempt to characterize in a general way the source of injustice toward women : humanist feminism ('the sameness approach'), gynocentric feminism ('the difference approach'), and dominance feminism. Offering an alternate perspective, the third section introduces two 'localizing' approaches, grounded in postmodernism and identity politics, respectively. Skeptical of theories that attempt to analyze social phenomena across history and culture, authors in this section challenge, rather than answer, the text's organizing questions. The final section explores the relationship of feminism theory to three liberatory projects - postcolonialism, neo-materialism, and queer theory - that do not characterize themselves as feminist, yet take gender as a significant category of analysis. Each section opens with an introduction and each essay is followed by helpful study questions. the majority of the essays are presented in their entirety. Theorizing feminisms underscores the strong connection between feminist theory and practice by including essays that illustrate important political inspirations or applications of each theoritical approach. It also presents versions of the same approach from various points in history, revealing feminist theory to be dynamic and evolving, rather than static. Ideal for interdisciplinary courses in feminist theory, this volume will also serve as an invaluable reference for current and future generations of theorists."
Section: 1 vol. (XIX-564 p.) ; 24 x 19 cm
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; essentialisme; intersectionnalité; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; thématiques; théorie féministe

Precarious life: The powers of mourning and violence - Butler, Judith (Verso, 2004)
Responding to the US’s perpetual war, Butler explores how mourning could inspire solidarity.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; discipline; guerre; histoire et politique; médias; philosophie; périodes historiques; régions géographiques; sciences humaines; thématiques; violences; états-unis; éthique

Marché au sexe - Rubin, Gayle; Butler, Judith P.; Sokol, Eliane (EPEL, 2001)
"Aucun amateur de cuisine épicée ne se verra privé de liberté ou victime d'ostracisme pour avoir satisfait ses papilles gustatives. En revanche, on peut être jeté en prison pour trop aimer les chaussures en cuir. De même, l'homosexualité, le sida, la pornographie, le transsexualisme, et aujourd'hui la pédophilie, donnent-ils lieu à ce que Gayle Rubin appelle une " panique sexuelle ". Chaque panique désigne une minorité sexuelle, généralement inoffensive, comme population-cible. Au terme du processus, celle-ci se trouve décimée, et la société tout entière, juridiquement et socialement, réorganisée. Gayle Rubin a jeté les bases d'un champ autonome d'études sur le sexe où désir, jouissance et diversité érotique, pourraient trouver leur raison théorique et politique. Les trois textes publiés ici s'inscrivent dans une filiation politique (le féminisme, la nouvelle gauche, les luttes antiracistes, les luttes pour les droits civiques) et théorique (les sexologues, Freud, Lacan, Marx, Foucault, Derrida). Les paradigmes ne valent rien sans l'enquête de terrain, et rien non plus s'ils ne s'actualisent en choix de stratégie et de tactique politiques. L'ensemble s'éclaire du partiel, le partiel de l'ensemble. Nous sommes loin ici du communautarisme béat qu'on prête parfois en France aux intellectuels américains. Qu'on lise les critiques acerbes de Judith Butler sur les replis identitaires : les lesbiennes n'ont rien d'autre en commun que leur expérience du sexisme et de l'homophobie. Ou ses réserves sur le coming out : " La sexualité reste-t-elle sexualité quand elle est soumise à un critère de transparence et de révélation? Une quelconque sexualité serait-elle possible sans cette opacité qui a pour nom inconscient? " Gayle Rubin et Judith Butler soulignent constamment la nécessité de ne pas troquer une violence contre une autre, une démonologie religieuse contre une démonologie laïque, laissant ainsi sa chance à l'érotologie moderne. (Éditeur).
Contenue: Entretien : Marché au sexe / Gayle S. Rubin et Judith Butler – Penser le sexe / Gayle S. Rubin – Imitation et insubordination du genre / Judith Butler.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; hétérosexisme; identités LGBTQIA2+; lesbianisme; lit3220; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex3383; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; théories féministes; transféminisme; états-unis